2007
DOI: 10.1093/cercor/bhm159
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Premotor Cortex Exerts State-Dependent Causal Influences on Activity in Contralateral Primary Motor and Dorsal Premotor Cortex

Abstract: During voluntary action, dorsal premotor cortex (PMd) may exert influences on motor regions in both hemispheres, but such interregional interactions are not well understood. We used transcranial magnetic stimulation (TMS) concurrently with event-related functional magnetic resonance imaging to study such interactions directly. We tested whether causal influences from left PMd upon contralateral (right) motor areas depend on the current state of the motor system, involving regions engaged in a current task. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
177
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(202 citation statements)
references
References 86 publications
24
177
0
1
Order By: Relevance
“…In previous studies, it has been demonstrated that while resting hands, interhemispheric PMd-M1 interactions are inhibitory (Mochizuki et al, 2004;Ni et al, 2009) but may turn into strictly timed and short-lasting facilitation during the premovement period (Koch et al, 2006;O'Shea et al, 2007;Liuzzi et al, 2010). By combining TMS and fMRI, Bestmann et al (2008) showed that a TMS pulse over the PMd elicits different effects on the motor regions of the opposite hemisphere depending on the state of the motor system. During hand grip, TMS led to activity increases in contralateral PMd and M1, whereas activity decreases were observed when the hands were at rest (Bestmann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it has been demonstrated that while resting hands, interhemispheric PMd-M1 interactions are inhibitory (Mochizuki et al, 2004;Ni et al, 2009) but may turn into strictly timed and short-lasting facilitation during the premovement period (Koch et al, 2006;O'Shea et al, 2007;Liuzzi et al, 2010). By combining TMS and fMRI, Bestmann et al (2008) showed that a TMS pulse over the PMd elicits different effects on the motor regions of the opposite hemisphere depending on the state of the motor system. During hand grip, TMS led to activity increases in contralateral PMd and M1, whereas activity decreases were observed when the hands were at rest (Bestmann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…By combining TMS and fMRI, Bestmann et al (2008) showed that a TMS pulse over the PMd elicits different effects on the motor regions of the opposite hemisphere depending on the state of the motor system. During hand grip, TMS led to activity increases in contralateral PMd and M1, whereas activity decreases were observed when the hands were at rest (Bestmann et al, 2008). Thus, PMd appears to exert task-dependent influences over the opposite motor regions.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to motor output, it is thought that premotor cortex assumes a focusing role by modulating the activity of interneurons in M1 (MĂŒnchau et al, 2002). Recent studies using TMS (and combined fMRI) in humans suggest a functional influence of (left) PMd upon the opposite PMd (and M1) that is strongly state dependent: varying in accordance with the nature of the task being performed by the ipsilateral limb (Bestmann et al, 2008). During movement preparation, there is a corresponding influence of (right) PMd on opposite M1, which precedes interhemispheric interactions between the homologous primary motor areas (Liuzzi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it has been reported that transcranial magnetic stimulation of the PMd changes excitability of the PMd and MI of the contralateral hemisphere (Bestmann et al 2008;Koch et al 2006Koch et al , 2007Mochizuki et al 2004), most likely via callosal connections (Di Lazzaro et al 1999;Ferbert et al 1992). Corresponding to these results, functional magnetic resonance imaging studies have demonstrated that the bilateral PMd was activated when conditional cues were applied to perform movements (Iacoboni et al 1998;Kurata et al 2000).…”
Section: Introductionmentioning
confidence: 99%